2004
DOI: 10.1073/pnas.0401319101
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-type assembly of FeS centers in the hydrogenosomes of the amitochondriate eukaryote Trichomonas vaginalis

Abstract: Mitochondria are the site of assembly of FeS centers of mitochondrial and cytosolic FeS proteins. Various microaerophilic or anaerobic unicellular eukaryotes lack typical mitochondria (''amitochondriate'' protists). In some of these organisms, a metabolically different organelle, the hydrogenosome, is found, which is thought to derive from the same proteobacterial ancestor as mitochondria. Here, we show that hydrogenosomes of Trichomonas vaginalis, a human genitourinary parasite, contain a key enzyme of FeS ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
106
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 50 publications
4
106
1
1
Order By: Relevance
“…Posterior probabilities for some groups are shown, with a value of 1.0 representing maximum support. The strongly supported groups have also been recovered in previously published analyses using different methods, including maximum-likelihood, and different support measures including bootstrapping (Horner et al 1999;Rotte et al 2001). examined (Katinka et al 2001;LaGier et al 2003; but only the Trichomonas hydrogenosome (Sutak et al 2004) and Giardia mitosome (Tovar et al 2003) have actually been demonstrated to contain the pathway. Entamoeba is so far unique among eukaryotes in that it has lost the mitochondrial homologues of IscS and IscU (Loftus et al 2005), and instead it possesses genes for the homologous proteins NifS and NifU, acquired through horizontal gene transfer from a bacterium related to Campylobacter (Ali et al 2004;van der Giezen et al 2004).…”
Section: Conclusion Speculations and Outlookmentioning
confidence: 61%
“…Posterior probabilities for some groups are shown, with a value of 1.0 representing maximum support. The strongly supported groups have also been recovered in previously published analyses using different methods, including maximum-likelihood, and different support measures including bootstrapping (Horner et al 1999;Rotte et al 2001). examined (Katinka et al 2001;LaGier et al 2003; but only the Trichomonas hydrogenosome (Sutak et al 2004) and Giardia mitosome (Tovar et al 2003) have actually been demonstrated to contain the pathway. Entamoeba is so far unique among eukaryotes in that it has lost the mitochondrial homologues of IscS and IscU (Loftus et al 2005), and instead it possesses genes for the homologous proteins NifS and NifU, acquired through horizontal gene transfer from a bacterium related to Campylobacter (Ali et al 2004;van der Giezen et al 2004).…”
Section: Conclusion Speculations and Outlookmentioning
confidence: 61%
“…Cysteine desulfurase (IscS) and a scaffold protein (IscU) carry out the crucial steps in biosynthesis of Fe-S centers. In eukaryotes, this process takes place exclusively in double membrane-bound organelles including mitochondria (11), hydrogenosomes (12), and chloroplasts (13). Phylogenetic analyses placed the Giardia IscS (GiiscS) within the mitochondrion͞ hydrogenosome clade (10,14).…”
mentioning
confidence: 99%
“…Mitosomal proteins were stained in fixed G. intestinalis and T. vaginalis cells with mouse ␣-HA mAb (12). In double-labeling experiments, G. intestinalis clathrin heavy chain, disulfide isomerase, and GiiscU were detected with rabbit polyclonal Abs (A. Hehl, University of Zürich, Zürich; ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations